CO51 | Novel biomarkers of neurological damage in acute immune-mediated thrombotic thrombocytopenic purpura (Bleeding, Thrombosis and Vascular Biology)
Background: Central nervous system (CNS) involvement is well-documented in acute immune-mediated thrombotic thrombocytopenic purpura (iTTP). Glial fibrillary acidic protein (GFAP), a marker of astrocytic injury, and neurofilament light chain (NfL), an indicator of axonal degeneration, are emerging biomarkers of CNS damage, as demonstrated by their associations with conditions such as stroke, dementia, and neuroinflammation. The role of these neurobiomarkers in iTTP has never been investigated.